The don't panic pantry cookbook : mostly vegetarian comfort food that happens to be pretty good for you - Galuten, Noah (Alfred A. Knopf, 2023)
"Delicious, nutritious, umami-heavy, well-balanced recipes for accessible whole-food meals, by the food writer and co-host of Don't Panic Pantry. As the world changes around us, we are constantly vacillating between two different versions of ourselves: the one who wants to be healthier and the one who wants to be excited, or comforted, by the food that we eat. We all want to eat "better," but what does that mean? This book is here to say: Don't Panic. In this age of too much information, Noah Galuten has refined his home cooking philosophy to a few key points: 1.Too much of any one thing is bad; 2. Balance is good; 3. Refined sugar is bad (and it is hiding everywhere); 4: Heavily processed food is bad (this is where most of the sugar is hiding); 5. We should eat less meat, and eat higher quality meat instead; 6. We should be focused on fiber instead of protein; 7. Stock your pantry to make home cooking the more convenient option. Here, the host of the IGTV's hit cooking show "Don't Panic Pantry" gives us new favorite go-to recipes like a Chef Salad with Probiotic Ranch and Cheddar Croutons, and Pasta with Rosemary-Bacon Tomato Sauce (or a vegetarian version using dried mushrooms instead). There are recipes for a 30-second Vegan Tahini Dressing that will become your new favorite dip; there's a recipe for Miso Roast Chicken with Vegetables that you can prep in advance and leave in the fridge for several hours, or even a day, that makes a one-pan dinner for your entire family. But it's also-for when you really need it-the fresh herbed panko crusted Mozzarella Marinara that made his famously funny wife, comedian Iliza Shlesinger, break down in tears. Here are your pantry staples for the future"--